Flexible-resource coordination supply recovery of active distribution network considering multiple demand responses - Bingbing, Chen; Jiateng, Liu; Haotian, Wu; Haiwei, Wang; Yunfan, Chen (Frontiers in Energy Research, 2025)
As the risk of extreme fault conditions to power supply reliability escalates, the importance of supply recovery within active distribution networks (ADNs) is exponentially increasing. However, the utilization of a single resource strategy is insufficient to fully exploit the supply recovery potential of the ADN’s diverse and flexible resources. Therefore, a flexible resource coordination supply recovery for ADN considering multiple demand responses is proposed. This strategy utilizes distributed generation (DG) and energy storage system (ESS) as distributed power supply units, and involves the operational flexibility of soft open points (SOPs) to couple DGs with ESSs. Meanwhile, the demand response consisting of transferable and interruptible loads is taken into account, with its load regulation capability harnessed to supply recovery. A supply recovery model is established to coordinate the flexibility of source, network, and demand sides, which is further transformed into a second-order cone programming (SOCP) model to enhance solution efficiency with accuracy preservation. Simulations conducted on a modified IEEE 33-node system validate the effectiveness of the proposed strategy in maximizing supply recovery.